Energy evaluation of a bio-inspired gait modulation method for quadrupedal locomotion. (4th August 2015) - Fukuoka, Yasuhiro; Fukino, Kota; Habu, Yasushi; Mori, Yoshikazu
Abstract: We have proposed a bio-inspired gait modulation method, by means of which a simulated quadruped model can successfully perform smooth, autonomous gait transitions from a walk to a trot to a gallop, as observed in animals. The model is equipped with a rhythm generator called a central pattern generator (CPG) for each leg. The lateral neighbouring CPGs are mutually and inhibitorily coupled, and the CPG network is hardwired to produce a trot. Adding only the simple feedback of body tilt to each CPG, which was based on input from the postural reflex, led to the emergence of un-programmed walking and galloping at low and high speeds, respectively. Although this autonomous gait transition was a consequence of postural adaptation, it coincidentally also resulted in the minimization of energy consumption, as observed in real animals. In simulations at a variety of constant speeds the energy cost was lower for walking at low speeds and for galloping at high speeds than it was for trotting. Moreover, each gait transition occurred at the optimal speed, such that the model minimised its energy consumption. Thus, gait transitions in simulations that included the bio-inspired gait modulation method were similar to those observed in animals, even from the perspective of energy consumption. This method should therefore be a preferred choice for motion generation and control in biomimetic quadrupedal locomotion.